Optimization and control of economic dispatch for power systems - 239080 Theng, Soon Teck (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001